REKONSTRUKSI DAN ADAPTABILITAS TEORI PERTINGKATAN NORMA DALAM IJTIHAD PENEMUAN HUKUM ISLAM - Subky, A Tajus; Syukri, Syukri; Zahra, Arlisa Siti (STIT Sunan Giri Bima, 2024)
This research seeks to examine in depth the deepening and reconstruction of the theoretical concepts of norm development and legal discovery. This research will use a qualitative research method with a type of literature study that analyzes pre-existing theories, concepts and phenomena. The results of the research can be formulated as follows: first, Islamic law has a structure of levels of legal norms, but the validity of Islamic legal norms (syar'i law) is not formal validity which is determined by a higher norm underlying the creation of these norms, as is the theory of the formal validity of legal norms. Second, there are three hierarchical levels of basic norms in Islamic law 1). al-mabadi' al-asasiyyah/al-qiyam al-asasiyyah (basic principles of Islamic law/basic values of Islamic law), 2). al-usul al-kulliyyah (general principles/general principles of Islamic law), 3). al-ahkam al-far'iyyah /al-furu’ (detailed/concrete legal provisions). Third, the existence of a theory of increasing norms in Islamic law can answer the problems of Islamic law which are not only seen in taklifi and wad'i law which are concrete sharia law, but must be seen from the perspective of general principles of law and universal principles so that it can answer the problems of all people.